1990
DOI: 10.1037/0022-0167.37.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction and eating-related problems on the college campus: Usefulness of the Eating Disorder Inventory with a nonclinical population.

Abstract: The Eating Disorder Inventory (EDI) was administered to 3 female undergraduate samples representing 2 campuses (N = 1,506). Subjects also provided information on family demographics and on eating, dieting, and exercise habits and attitudes. Very high rates of body dissatisfaction were reported. EDI factor analysis yielded a 6-factor structure accounting for 41 % of the variance. The Eating Disorders factor was a combination of 3 EDI clinical scales (Drive for Thinness, Bulimia, and lack of Interoceptive Awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 35 publications
6
66
2
1
Order By: Relevance
“…Past research has found that women diagnosed with an eating disorder and women displaying symptoms of an eating dysfunction show high levels of body dissatisfaction, weight preoccupation, perfectionist tendencies, and maladaptive eating attitudes and behaviors (Garner et al, 1984;Klemchuk et al, 1990). The present study compared women with an eating disorder to women with an eating dysfunction on these factors, taking them into account simultaneously.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Past research has found that women diagnosed with an eating disorder and women displaying symptoms of an eating dysfunction show high levels of body dissatisfaction, weight preoccupation, perfectionist tendencies, and maladaptive eating attitudes and behaviors (Garner et al, 1984;Klemchuk et al, 1990). The present study compared women with an eating disorder to women with an eating dysfunction on these factors, taking them into account simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…Of important note, women displaying symptoms of an eating dysfunction have been found to display similar difficulties compared to a clinical population of women diagnosed with eating disorders (Klemchuk, Hutchinson, & Frank, 1990). Garner, Olmsted, Polivy, and Garfinkel (1984) compared women classified as weight preoccupied, meaning that they were highly concerned about their weight, to women diagnosed with anorexia nervosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Klemchuk, Hutchinson, and Frank's (1990) factor analytic study yielded a six factor model, accounting for only 41% of the total variance and further recommended more studies to examine the use of two main factors for the purposes of disordered eating screening. Moreover, Garner (1991) recommended the subscales be used individually as the low intercorrelation between subscales suggests they are measuring distinct constructs instead of a general measure of eating disorder symptomatology.…”
Section: Measuring Disordered Eating Attitudesmentioning
confidence: 99%
“…There are many factors that can play a role in the development of eating disorders such as body dissatisfaction, drive for thinness, and social physique anxiety (Lofton, 2000). The college environment and experience often tend to drive many of these factors (Klemchuk, Hutchinson, & Frank, 1990).…”
Section: Introductionmentioning
confidence: 99%